Progress and Prospect of Ultrasonic Vibratory Cutting Research - Li, Quyun; Cai, Xinyuan; Li, Wei; Tan, Zhenhua; Yang, Canyu (Manufacturing Technology Journal, 2023)
Ultrasonic vibration cutting technology for processing difficult-to-cut materials proposed a new machining method to improve the cutting performance, is an effective measure to improve the surface quality and cutting efficiency, widely used in titanium alloys and other difficult-to-cut materials. This paper is based on the development of related technology research at home and abroad, first from one-dimensional ultrasonic vibration cutting, two-dimensional ultrasonic vibration cutting, three-dimensional ultrasonic vibration cutting three dimensions to high-speed ultrasonic vibration cutting to carry out the analysis, and then from each dimension of turning, drilling, grinding and milling and other different ways of cutting mechanism, cutting force, surface quality, device development, tool design and other directions of the systematic analysis and research. The analysis results show that ultrasonic vibration cutting technology provides new technical solutions and methods to solve the problems of low efficiency and low dimensional accuracy in processing difficult-to-cut materials by ordinary cutting technology, and can provide technical support for the processing of difficult-to-cut materials. Finally, it looks forward to the future trend of ultrasonic vibration cutting technology: in the future, the integration with five-axis machining technology, additive manufacturing technology, microscopic inspection technology, 5G communication technology and other cutting-edge technologies will be the development direction of ultrasonic vibration cutting technology.
Keywords: Ultrasonic vibration; Cutting; Cutting force; Surface quality; Devices and tools